Violence against married women living in Jaffna, Sri Lanka: A retrospective study of police reports - Wickramasinghe, S. W.; Gamage, W. G. E. P.; Meshel, M. S. S.; Perera, A. S. T. C.; Kitulwatte, S. C.; Edirisinghe, P. A. S.; Sanchithan, R. P. (International Conference on Child Protection 2025, University of Kelaniya, Sri Lanka., 2025)
Background: Violence perpetrated by legally married husbands against their wives is a significant social and public health concern. This study described the prevalence, nature and patterns of such violence reported to the Jaffna Police during a period of two years, identifying key risk factors and potential interventions. Method: A descriptive retrospective study was conducted using police records of Child and Women Bureau of Jaffna Police Division where 200 cases reported from July 2021 to July 2023 were analyzed using descriptive statistics. Results: The majority of the victims (71%; were in the 25-45-year range. Rural areas recorded the highest number of cases (57%) while urban areas had the least (3.5%). Alcohol and drug use were the primary causes (56%), followed by extramarital affairs (21.5%). The most common complaint purpose was counseling (55.5%). Emotional (49.5%) and physical violence (46.5%) were the most frequent types of violence. Police counselling was the most common intervention (52.5%). Most incidents were first-time reports (61%). About 75.5% of cases involved daily violence. Home treatment was preferred by the majority (52.5%) It was identified that 67% of the cases were settled by the Police. Conclusions: The findings of this study highlight the widespread prevalence of intimate partner violence in married couples within the Jaffna region, with alcohol and substance abuse, extramarital affairs, and communication issues emerging as key contributing factors. The high prevalence of daily violence and predominance of first-time reports suggest a critical gap in early intervention and support systems. These findings emphasize the urgent need for a comprehensive, multi sectoral approach to combat intimate partner violence.
Keywords: Intimate partner violence; physical violence; emotional